Crust beneath the northwestern Deccan Volcanic Province, India: Evidence for uplift and magmatic underplating. Issue 5 (21st May 2015) - Rao, K. Madhusudhan; Kumar, M. Ravi; Rastogi, B. K.
Abstract The northwestern Deccan Volcanic Province of India and its pericratonic rift basins were reactivated during different stages after the breakup of India from the Gondwanaland and collision with the Asian plate. In this study, we present results of crustal thickness and average crustal Vp/Vs ratios beneath this plume‐affected region using common conversion point imaging and H‐k stacking analysis of 6893 receiver functions using data from a network comprising 58 broadband seismic stations sited on diverse tectonic terrains. We find large variations in crustal thickness, with the Moho depths varying from 28 to 43 km in the Kachchh rift, 28 to 38 km in the Cambay rift, 39.5–41.5 km in the north and eastern parts of the Cambay rift, and 29 to 39 km in the Saurashtra region and South Gujarat. A Moho upwarp of 6 to 7 km in the Saurashtra region can be attributed to positive buoyancy and uplift due to thermal influx affected by the Reunion plume. High crustal Vp/Vs ratios beneath the Kachchh rift (1.8 to 2.05), coastal areas of Saurashtra (1.75 to 2.06), and North Gujarat (1.81 to 1.85) indicate dominance of a mafic/ultramafic crust. High regional heat flow, high electrical conductivity, large intracrustal S wave velocity reduction, and high average crustal Poisson's ratios are consistent with partial melt related to the process of magmatic underplating in the lower crust. At other stations, the crust appears to be felsic with Vp/Vs ratios in the range of 1.57 to 1.76.